KOMPETENSI KEPRIBADIAN GURU PAI DALAM MEMBINA AKHLAK PESERTA DIDIK DI SD NEGERI 2 BANDAR DALAM KECAMATAN SIDOMULYO KABUPATEN LAMPUNG SELATAN TAHUN PELAJARAN 2025/2026 - DWI PUSFITA LAYLI (UNISAN JURNAL, 2025)
This research aims to conduct an in-depth analysis of the personality competence of Islamic Religious Education (PAI) teachers in fostering students’ morals at SDN 2 Bandar Dalam Sidomulyo. Personality competence is one of the essential aspects that every teacher, particularly Islamic education teachers, must possess. The success of moral development among students largely depends on the teacher’s character, integrity, and exemplary behavior in carrying out their duties. PAI teachers are expected not only to master cognitive and pedagogical aspects but also to embody strong moral integrity, emotional maturity, and deep spirituality to serve as true role models (uswah hasanah) for their students. This study employs a qualitative descriptive approach. Data were collected through direct observation, in-depth interviews with PAI teachers, the principal, and several students, as well as documentation of teaching and religious activities at the school. The data were analyzed using qualitative analysis techniques involving data reduction, data presentation, and conclusion drawing. The findings show that PAI teachers at SDN 2 Bandar Dalam Sidomulyohave demonstrated commendable personality competence in their efforts to guide and nurture students’ moral development. They exhibit stable, mature, wise, and authoritative personalities, with high moral and spiritual integrity. This is reflected in their daily behavior, characterized by patience, honesty, discipline, responsibility, and empathy toward students. Moral development is carried out through various approaches such as modeling, habituation of religious practices like congregational prayers, Qur’an recitation, and moral counseling conducted in a communicative and affectionate manner. Furthermore, the success of moral education is supported by strong collaboration among teachers, school leaders, and parents in instilling religious and ethical values in students. The school’s Islamic atmosphere and character-oriented culture further reinforce students’ moral formation. However, several challenges were also identified, such as the negative influence of social media and the inconsistency of some students in applying moral values outside the school environment. In conclusion, the personality competence of PAI teachers plays a vital and significant role in fostering students’ moral and character development. Islamic education teachers not only serve as instructors but also as moral exemplars who embody Islamic values in daily life. Continuous development of teachers’ personality competence is therefore essential to strengthen the moral education process and produce a generation that is faithful, knowledgeable, and of noble character.